Striking at the Sacred: The Violence of Prayer, 1960-1969 - Shearer, Tobin Miller (Open theology, 2015)
This essay explores the complex relationship between public prayer and violence during ten years of the Civil Rights Movement. During the 1960s and throughout the long civil rights era, activists who used the race-based, highly performative act of public prayer incited violence and drew the nation’s attention to the black freedom struggle. Study of the public prayers that led to violence further suggests that the introduction of prayer into public space acted as a conduit of moral judgment even when intended as a bridge of connection, a pattern that suggests the exercise of public prayer can be a catalyst for violence.